Poly(sulfur ylides): a new class of zwitterionic polymers with distinct thermal and solution behaviour. Issue 30 (14th July 2022) - Poulladofonou, Georgia; Neumann, Kevin
Abstract : Readily available poly(sulfur ylides) are described as a new class of zwitterionic polymers that show distinct solution and thermal behavior. Abstract : Zwitterionic polymers have emerged as an important class of hydrophilic polymers and found widespread applications not only in biomedical science but also in nanotechnology as antifouling coatings, drug delivery vesicles and electronic conductors. For such applications, new structural forms of zwitterionic polymers with distinct functions are in high demand. However, to this day, their design is mostly limited to polybetaine and polyampholyte scaffolds, bearing a stoichiometric amount of positive and negative charge either in a single repeating unit or across the polymer, respectively. Here, we report on the synthesis and characterization of poly(sulfur ylides), a rarely encountered class of zwitterionic polymers and demonstrate that this new form of zwitterionic polymers displays not only a remarkable stability but also distinct solution and thermal behavior. We show that the readily available poly(sulfur ylides) are a valuable addition to the chemical toolbox of polymeric materials and have the potential to become an attractive alternative to polybetaines and polyampholytes.